Smart City Architecture Development Framework (SCADEF) - Yuli Adam Prasetyo; Ichwan Habibie (Society of Visual Informatics, 2022)
Smart City is a city that implements the latest technologies, such as big data, IoT, Artificial Intelligence, and other new technologies. Smart City has different system characteristics than other systems. Smart City involves several independent stakeholders, so the development of a smart city needs to be designed with a system analysis system and service-based planning. Smart City Architecture Development Methodology (SCADM) has been defined from the previous research. However, the existing Enterprise Architecture approach has yet to specify the artefact to complete the framework. This study recommends the Smart City Architecture Framework (SCADEF) as a comprehensive Enterprise Architecture Framework to develop Smart City Architecture. The architecture framework produced by SCADEF becomes the proposed architecture framework for realizing Smart City. SCADEF consists of SCADM, Meta-model Smart City Architecture Development Methodology Artefact, and guidelines by the implementation SCADEF. The research uses observation, classification, and construction methodologies in Information System Design Methodology. In addition, this study also tested the framework by implementing it on city objects. This implementation is a practical test tool for the resulting enterprise architecture framework. This study implemented SCADEF in the education and health field at Bandung Smart City. Implementing testing on the implementation of SCADEF is to explain the implementation in Bandung Smart City and ask for an assessment from enterprise architecture experts. The results of the expert assessments were calculated statistically to assess the methodology, artefacts, and uses. The measurement results show that SCADEF can be accepted and used to develop enterprise smart city architecture.